Critiquing representations of intellectual disability in occupation-based literature - Rachel Reparon; Pamela Block; Ann Fudge Schormans; Debbie Laliberte Rudman; Gail Teachman (Scandinavian Journal of Occupational Therapy)
Background Within and beyond occupation-based scholarship, concerns abound regarding the pervasiveness of discourses that promote a negative, deficit-based view of intellectual disability and associated consequences for disabled people’s lives. Such representations risk reducing the complexities of human doing and being and can limit the occupational possibilities of this group. Yet, there is a lack of critically reflexive research exploring how disability is discursively constructed in occupation-based literature.Aims/Objectives This paper critically analyses representations of intellectual disability within occupation-based literature. It considers the influence of such representations on the occupational possibilities of people labelled intellectually disabled.Methods This review employed a critical interpretive synthesis of 21 peer-reviewed articles from occupational therapy and occupational science that focused on intellectual disability.Results Three analytic threads were identified as contributing to how intellectual disability was represented across the reviewed literature: habilitating expected doings, becoming productive citizens, and activated, but insufficient.Conclusion & significance Occupation-based discourses have powerful influence within society, particularly within occupational therapy, regarding understandings of intellectual disability and how these shape occupational possibilities for persons labelled intellectually disabled. Drawing attention to taken-for-granted representations of intellectual disability is essential to promote transformative occupational therapy practice and enhance occupational possibilities for this population.